Penerapan Round Table Berdasarkan Nilai Islami Terhadap Peningkatan Kemampuan Berpikir Kritis Matematis Siswa - Nenden Suciyati Sartika (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2020)
This research aims to develop a Round Table learning model that is cooperative learning based on Islamic values to see an increase in mathematical critical thinking students skills. The method developed in this research is a quasi experimental method. The result of this research is that by applying the Round Table learning model based on Islamic values, mathematical thinking students skills can be improved. The development of this Round Table learning model really stimulates students to think criticly.